Penggunaan Metode Cooperativescript dalam Meningkatkan Hasil Belajar Siswa Madrasah Tsanawiyah Al Jauharen Tanjung Johor Kota Jambi - Nazifah Nazifah (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2019)
This research aims to improve student learning result of Madrasah Tsanawiyah Al JauharenTanjung Johor Jambi by using cooperative script method in integrated science learning.This research is PTK (Classroom Action Research),using cooperative script method.Data collection conducted with observation sheet and test, which is conducted in the end of each cycle. The subjects of this research are students of class VII A Madrasah Tsanawiyah Al JauharenTanjung Johor Jambi numbered 30 people.In the application of this cooperative script method, gained an improvement in student learning result in each cycle. Cycle I average score of students is 72.3 with 66.67% student’s completion index. Cycle II average score of students is 77,37 with 80% student’s completion index.Improvement of cooperative script application succeed can be seen from the gain index, which cycle I increase 0.6 (medium), cycle II 0.7 (high). From the results of this research it’s recommended that cooperative script method can be applied by teachers in science learning in school, to improve learning result.